Renewable energy from the waste soles through thermal pyrolysis-A novel approach - Hashem, MA; Paul, AC; Hosen, S; Hasan, A (Bangladesh Journal of Scientific and Industrial Research, 2017)
Footwear is a booming sector in Bangladesh. Disposing of process residues from the footwear industries, especially production waste of thermoplastic rubber and polyvinyl chloride soles as well as human used soles is a big concern due to its non-biodegradability. In this work, waste thermoplastic rubber (TPR) and polyvinylchloride (PVC) soles were used as an energy source through the fixed-bed-fire-tube heating pyrolysis to reduce the pollution load. The experiments were performed at varying temperature within the range of 250°C to 450°C at every 100°C interval for each case. In pyrolysis oil, char and gas were produced from the both TPR and PVC soles; temperature increment was created more percentage of oil from the both soles. At same condition TPR sole was produced 12.3% more oil than PVC sole. The pyrolytic oils were made fractional distillation; obtained liquids were relatively greater in volume and low boiling range. The obtained liquids from the fractional distillation were exhibited more light fractions present in the pyrolytic polyvinyl chloride oil (PPVCO) than pyrolytic thermoplastic rubber oil (PTPRO). The process could be optimized for the large scale, which will offer advantages to reduce the environmental impact as well as the production of new product from the waste soles. Bangladesh J. Sci. Ind. Res. 52(2), 141-146, 2017